The role of peroxisomes in osteoblast differentiation and functions - Fan, Wei; Justus Liebig University Giessen (My University, 2014)
Peroxisomes are cell organelles that play critical roles from yeasts to humans during development, differentiation and morphogenesis and host a wide range of essential metabolic pathways such as lipid metabolism and the free radical detoxification. The importance of normal peroxisomal function and signaling in bone development is demonstrated by patients with Zellweger syndrome (ZS) and ZS mouse models. Zellweger syndrome is a human disorder caused by mutations in peroxisomal biogenesis genes. Patients exhibit typical skeletal deformations in addition to other developmental defects. Similarly, SIRT1, a highly conserved NAD+-dependent protein deacetylase, regulates lipid and antioxidative metabolism as well as proliferation pathways to extend mammalian lifespan, through deacetylation of histones and central transcription factors and cofactors, such as PPARs, FoxOs and RUNX2. By using the Pex11 and Pex13 KO animal models with a Zellweger phenotype including strong ossification defects and skeletal deformation, we found that the differentiation and maturation processes in primary osteoblasts isolated from these animals were dramatically delayed when peroxisome biogenesis and peroxisomal enzymatic function were dysfunctional. Furthermore in osteoblasts of these ZS mouse osteoblasts, cell apoptosis and cell cycle were severely altered as well as the DNA binding capability of PPARs, FoxOs and RUNX2 together with increasing cellular oxidative stress and lipid toxicity. Interestingly, disturbances within the process of ossification and osteoblast differentiation were observed also in the Sirt1 KO mouse model. Moreover, the peroxisome biogenesis and their enzymatic functions were significantly reduced and oxidative stress was increased. Interestingly we could show that SIRT1 also maintains homeostatic RA signaling by regulating the subcellular localization of CRABPII through its deacetylation activity. Therefore, the nuclear accumulation of the hyper-acetylated CRABPII and elevated RA signaling were induced by SIRT1 deficiency, which resulted in the accelerating differentiation of mesenchymal stem cells (MSCs) and developmental defects in Sirt1 KO mice. Whether the deacetylation function of SIRT1 may have been altered in Pex11 and Pex13 KO osteoblast due to the strong downregulation of the SIRT1 abundance and nuclear translocation has to be investigated in future. Additionally, the capability to enhance osteoclastogenesis was increased in Sirt1 KO osteoblast via an unbalanced RANKL/OPG system.Taken my results together and in respect to our previous data and the latest literature, the functions of peroxisomes in these cell types are summarized. The peroxisome contributes to the maintenance of the homeostasis of lipid metabolism and cellular redox stress. Peroxin gene deletion induced peroxisomal dysfunction which results in increased cellular oxidative stress, lipid toxicity and possible alterations in the deacetylation state of SIRT1. The activity of the transcription factors PPARs, FoxOs and RUNX2 induced by oxidative stress and lipid accumulation might be altered by SIRT1 deacetylation, as well as the RA signaling and this interference may in part contribute to the severe changes of differentiation, cell cycle, apoptosis and proliferation process observed in osteoblast and ossification disturbance of ZS mice.
Keywords: ddc:610